Paper and other pulp based eco-friendly moulded materials for food packaging applications: a review - Dey, Ayan; Sengupta, Priyanka; Pramanik, Nilay Kanti; Alam, Tanweer (Journal of Postharvest Technology, 2020)
Pulp is one of cheap resources with abundant availability. Papers are made using pulp which finds tremendous use in packing the food products. Such materials are also can be recycled and reused to develop moulded articles useful for packaging applications and other food contact items like trays, cup, plate and pouches etc. Last decade has evidenced several advancements in manufacturing technologies and recycle technologies for paper and pulp based moulded articles. However, there are also many constrains and challenges that were faced during manufacturing of products. This review article covers the various papers and pulp based moulded articles that can be used as food contact materials along with their manufacturing and recycling technologies. Moreover, this article also briefs about various characterization techniques used to ensure the quality of paper and pulp based moulded articles. This information is beneficial in making progress in the development of moulded articles using paper and pulp.